Luxemburgi Zsigmond utazásainak gyakorlata az 1414. év példáján keresztül = Sigismund of Luxemburg's travels through the example of 1414 - Szanka Brigitta (Belvedere Meridionale, 2015)
Sigismund of Luxemburg because of his unique Western and Central-European travels constantly stands in the focus of foreign and Hungarian historical attention. The year 2014 is not only memorable due to the 600th jubilee of Sigismund’s coronation as king of Germany and the beginning of the Council of Constance, but this year also deserves more attention because of his travels. I wish to demonstrate the practice of royal travels through the examples of the above-mentioned political and ecclesiastical events. As far as Sigismund is concerned, it is worth examining the money-raising opportunities, and the related parallel journeys. Furthermore, the question of the king’s escort is also verz interesting, because from this year Queen Barbara and Nicholas II Garai, Palatine of Hungary who had been recently appointed to vicar stayed in the entourage of Sigismund. Besides, we cannot ignore the possibilities of fluvial transport in the case of two mentioned cities. I consider it important as well that the representative entries into the cities connected with ceremonial context was determining in both cases. Therefore, I examine the political and religious rites, the royal representation and the travels in close context.